The Effect of Applying Geofencing Technology on the Egyptian Customers' Purchasing Intention to Tour Services - Taha, Shaimaa; El-Mawardy, Ghadeer (جامعة المنصورة - كلية السياحة والفنادق, 2022)
Mobile-based marketing has been increasingly adopted by many enterprises‟ marketing campaigns with the dominance of smartphone usage all over the world. Geofencing technology is one of the innovative recent trends in this field that tracks consumers‟ locations in real-time and enables enterprises to personalize their marketing campaigns. This research aims to explain the fields of applying Geofencing technology in the tourism industry and how this technology can affect the Egyptian travel agencies‟ marketing campaigns and the Egyptian customers' purchasing intention for tour services. In this regard, a quantitative approach will be adopted using an online structured questionnaire in order to investigate the acceptance of this technology among the Egyptian customers and accordingly to their purchasing intention to tour services. Finally, conclusions and recommendations of research will be discussed.
Keywords: الخدمات السياحية -- التسويق الإلكتروني -- السياحة المصرية -- فيروس كورونا "كوفيد-19" -- وكالات السفر